2008
DOI: 10.4028/www.scientific.net/msf.600-603.855
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Electric Discharge Machining for Silicon Carbide Single Crystal

Abstract: In this study, we report electric discharge machining (EDM) as a new cutting method for silicon carbide (SiC) single crystals. Moreover, we discuss characteristics and usefulness of the EDM for the SiC. The EDM realized not only high speed and smooth cutting but also lower surface damage. Defect propagation in the EDM SiCs have been also estimated by etch pits observation using molten KOH, however, we confirmed the EDM has caused no damage inside the SiCs in spite of high voltage and high temperature during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Yamada et al [3] has found that wire electrical discharge machining (EDM) slicing of SiC could achieve a higher cutting speed and a lower surface warpage than diamond multi-wire saw. Kato et al [4] reported that wire EDM could result in a lower surface damage layer of SiC compared to the surface machined by a mechanical polishing process using diamond fine abrasive of 0.25 μm particle size. In their study, the EDM'd surface of SiC wafer became atomically flat surfaces after removing a layer of about 10∼25 μm thick from the EDM'd top surface.…”
Section: Introductionmentioning
confidence: 99%
“…Yamada et al [3] has found that wire electrical discharge machining (EDM) slicing of SiC could achieve a higher cutting speed and a lower surface warpage than diamond multi-wire saw. Kato et al [4] reported that wire EDM could result in a lower surface damage layer of SiC compared to the surface machined by a mechanical polishing process using diamond fine abrasive of 0.25 μm particle size. In their study, the EDM'd surface of SiC wafer became atomically flat surfaces after removing a layer of about 10∼25 μm thick from the EDM'd top surface.…”
Section: Introductionmentioning
confidence: 99%
“…EDM is the best choice for machining SiC ceramic because there is no contact between the tool electrode and workpiece during the process. However, conventional EDM such as die-sinking electrical discharge machining, wire electrical discharge machining (WEDM) and electrical discharge grinding (EDG) shows low efficiency when machining a large surface area on SiC ceramic [13][14][15]. Recently, EDM milling has been developed to improve the machining efficiency.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…EDM of SiC single crystal has been performed by Kato et al [7] . Klocke and Zunke [21] investigated the material removal mechanisms in polishing of SiC and they concluded that the MRR and dominating material removal mechanism depends strongly on material properties and machining parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is no physical contact between the electrode and workpiece and hence material hardness is not an issue. In the past few years, researchers have demonstrated successful machining of ceramics such as WC [2][3][4], SiC [5][6][7], SiN [8], Si 3 N 4 [9], ZrO 2 [10] using EDM process. Thus, it follows that EDM is suitable for machining ceramics.…”
Section: Introductionmentioning
confidence: 99%